If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3x + -6 = 8 Reorder the terms: -6 + 0.3x = 8 Solving -6 + 0.3x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 0.3x = 8 + 6 Combine like terms: -6 + 6 = 0 0 + 0.3x = 8 + 6 0.3x = 8 + 6 Combine like terms: 8 + 6 = 14 0.3x = 14 Divide each side by '0.3'. x = 46.66666667 Simplifying x = 46.66666667
| y=73 | | 4x^2-64x-80=0 | | 8=2x+24 | | -45k-18k^2+9k=0 | | 6x^3-3x+4=0 | | 7+2x=35 | | 0=-16t^2+5t+1255 | | 32x+65=0 | | 2xy+6x-8y= | | 4x+75=23 | | n-15x=6 | | (X-6)(X-6)3=147 | | 5m^2-26m-24=0 | | Y-8/3-1/3x2/3 | | 1+log(3x-1)=log(2x+1) | | 3x^2=15x+18 | | 3x(3x-10)=-24 | | cos(6x)-cos(2x)= | | x+30=40 | | 3x-8y+6y=8 | | (3x-5)(9x+1)=0 | | 2x^2=4(x-5) | | 12x^3+20x^2-8x=0 | | -5n(5n-7)=0 | | 12x^3+20x-8x=0 | | 6(4x-8)+8=24x-40 | | 0.33=ln | | 3x+1=3(x-8) | | 2y=-1.5x+38 | | a/9-=6 | | 12y^2-2=5y | | 3x^3-x^2+36X-12=0 |